The Sign Language Interpreting studies reader - Roy, Cynthia B., 1950-; Napier, Jemina (Benjamins translation library, 2015)
In Sign Language Interpreting (SLI) there is a great need for a volume devoted to classic and seminal articles and essays dedicated to this specific domain of language interpreting. Students, educators, and practitioners will benefit from having access to a collection of historical and influential articles that contributed to the progress of the global SLI profession. In SLI there is a long history of outstanding research and scholarship, much of which is now out of print, or was published in obscure journals, or featured in publications that are no longer in print. These readings are significant to the progression of SLI as an academic discipline and a profession. As the years have gone by, many of these readings have been lost to students, educators, and practitioners because they are difficult to locate or unavailable, or because this audience simply does not know they exist. This volume brings together the seminal texts in our field that document the philosophical, evidence-based and analytical progression of SLI work.